A Facile Oxidation of Tertiary Amines to Lactams by Using Sodium Chlorite: Process Improvement by Precise pH Adjustment with CO2 - Liu, Chaoyang; Sun, Haozhou; Qin, Cheng; Yang, Tiannuo; Zhang, Wenxian; Zhou, Yuan; Li, Yani; Jia, Zheng Robert; Chu, Changhu (Synlett, 2022)
By using cheap and innocuous sodium chlorite, a series of tertiary amines have been oxidized to the corresponding lactams with good selectivity and high yield. In this method, neither transition-metal catalyst nor oxidant was used. In the oxidation step, the pH of the sodium chlorite was precisely adjusted to pH around 6 using CO2, such pH is a compromise between oxidative properties, chemical stability, and unwanted precipitation. In addition, buffer salts are not necessary, which allows this oxidation reaction to be performed under safe and environmentally benign conditions.
Keywords: amine oxidation; sodium chlorite; transition-metal-free; carbon dioxide; pH adjustment